Komparasi Metode Isolasi DNA dalam Mendeteksi Gen toxR Bakteri Vibrio parahaemolyticus pada Udang Vaname (Litopenaeus vannamei) - Lestari, Nana (LPPM Universitas Terbuka, 2024)
Vibrio parahaemolyticus bacteria is one of the dangerous pathogens in vaname shrimp farming (Litopenaeus vannamei). Infection with this bacterium can cause mass mortality in shrimp and considerable losses for farmers. This bacterium also has a specific gene, the toxR gene, which is used to detect its presence. The successful detection of this bacterium determines the success of handling the disease it causes. The purpose of the study was to determine the optimal DNA isolation method in detecting the toxR gene of Vibrio parahaemolyticus bacteria in vaname shrimp. The research was conducted by means of molecular biology-based identification using two DNA isolation protocols, namely Chloroform and Boilling Lysis Buffer. Visualization results showed that toxR gene DNA appeared in samples isolated with Boiling Lysis Buffer in Tryptic Soy Broth (TSB) media culture preparation. This means that the Boiling Lysis Buffer method is a suitable DNA isolation method for detecting the toxR gene of the Vibrio parahaemolyticus bacteria in white shrimp.